"y(x)=\\displaystyle\\sum_{n=0}^{\\infin}a_nx^n"
"y'(x)=\\displaystyle\\sum_{n=1}^{\\infin}na_nx^{n-1}"
"y''(x)=\\displaystyle\\sum_{n=2}^{\\infin}n(n-1)a_nx^{n-2}"
"\\displaystyle\\sum_{n=2}^{\\infin}n(n-1)a_nx^{n-2}+x\\displaystyle\\sum_{n=1}^{\\infin}na_nx^{n-1}+(x^2+2)\\displaystyle\\sum_{n=0}^{\\infin}a_nx^n=0"
"\\displaystyle\\sum_{n=2}^{\\infin}n(n-1)a_nx^{n-2}+\\displaystyle\\sum_{n=1}^{\\infin}na_nx^{n}+\\displaystyle\\sum_{n=0}^{\\infin}a_nx^{n+2}+\\displaystyle\\sum_{n=0}^{\\infin}2a_nx^n=0"
"\\displaystyle\\sum_{n=0}^{\\infin}(n+2)(n+1)a_{n+2}x^{n}+\\displaystyle\\sum_{n=1}^{\\infin}na_nx^{n}+\\displaystyle\\sum_{n=0}^{\\infin}a_nx^{n+2}+\\displaystyle\\sum_{n=0}^{\\infin}2a_nx^n=0"
"\\displaystyle\\sum_{n=0}^{\\infin}(n+2)(n+1)a_{n+2}x^{n}+\\displaystyle\\sum_{n=1}^{\\infin}na_nx^{n}+\\displaystyle\\sum_{n=2}^{\\infin}a_{n-2}x^{n}+\\displaystyle\\sum_{n=0}^{\\infin}2a_nx^n=0"
"2a_0+3a_1x+2a_2+6a_3x+\\displaystyle\\sum_{n=2}^{\\infin}[(n+2)(n+1)a_{n+2}+na_n+a_{n-2}+2a_n]x^{n}=0"
"n=0\\implies 2a_2+2a_0=0\\implies a_0=-a_2"
"n=1\\implies 2a_2+6a_3x+a_1x+2a_0+2a_1x=0\\implies 6a_3+3a_1=0"
"a_1=-2a_3"
For "n=2,3,4,..." :
"(n+2)(n+1)a_{n+2}+na_n+a_{n-2}+2a_n=0"
"(n+2)(n+1)a_{n+2}+(n+2)a_n+a_{n-2}=0"
"a_{n+2}=-\\frac{a_{n-2}+(n+2)a_n}{(n+1)(n+2)}"
Answer:
"y(x)=a_0+a_1x-a_0x^2-\\frac{a_1}{2}x^3-\\frac{a_0+4a_2}{12}x^4+..."
Comments
Leave a comment